2018
DOI: 10.1016/j.jngse.2018.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring gas hydrate formation and transport in a flow loop with acoustic emission

Abstract: Experimental studies on flow loop allow estimating the amount of formed hydrate and their transport during time. The amount of hydrates formed spatially during flow is unknown together with the location of the beginning of sedimentation and plug. This experimental study was carried on to verify the use of acoustic emission (AE) to spatially follow the formation of hydrates but also sedimentation and agglomeration. The acoustic emission energy variations allowed to follow the emulsification, to identify the beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Lv et al experimentally demonstrated that the accumulation of hydrate particles is the key factor that leads to blockage under water-dominant flow conditions using focused beam reflectance measurements in a high-pressure loop. Cameirao et al verified the feasibility of using acoustic emission to monitor hydrate formation, accumulation, and plugging processes by conducting flow loop experiments. Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lv et al experimentally demonstrated that the accumulation of hydrate particles is the key factor that leads to blockage under water-dominant flow conditions using focused beam reflectance measurements in a high-pressure loop. Cameirao et al verified the feasibility of using acoustic emission to monitor hydrate formation, accumulation, and plugging processes by conducting flow loop experiments. Zhou et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lv et al 27 experimentally demonstrated that the accumulation of hydrate particles is the key factor that leads to blockage under water-dominant flow conditions using focused beam reflectance measurements in a high-pressure loop. Cameirao et al 28 verified the feasibility of using acoustic emission to monitor hydrate formation, accumulation, and plugging processes by conducting flow loop experiments. Zhou et al 29 visually demonstrated that the CO 2 hydrate formation rate increased as the initial pressure increased and decreased with an increase in temperature, flow rate, and liquid loading via a flow loop test.…”
Section: Introductionmentioning
confidence: 99%
“…Gas hydrate formation applied to flow assurance has been studied in a variety of bench- and pilot-scale experimental rigs, such as stirred cells, high-pressure rheometers, , rocking cells, , rock-flow cell, and flow loops. The different testing rigs are used exclusively or in combination with the purpose of providing information on the outcomes of the test that may be applicable to manage solid precipitation at field conditions. As seen in the literature mentioned above, the data obtained from different testing rigs use different methods and procedures, making the interpretation and application of the results subjective without clearly defined criteria for assessing solid transportability.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results showed that the agglomeration and formation of crystals could be detected from the amplitude of the acoustic signal. 3 Wang 4 designed a detection system of hydrate plugging in gas pipeline with the pressure wave propagation method; multiple plugging could be detected, and the location as well as degree of single hydrate plugging could be achieved. Xinghua et al proposed a new detection methodology of multiple leaks in a natural gas pipeline based on observer and mixed-integer partial differential equation constrained optimization.…”
Section: Introductionmentioning
confidence: 99%